Assessing the influence of sound parameters on crossmodal cuing in different regions of space - Lee, J; Spence, C (Elsevier, 2018)
To date, crossmodal spatial cuing research has primarily investigated spatial attention modulated by the positioning of auditory cues, without addressing the question of the role played by sound parameters such as intensity change, waveform structure, or duration. Therefore in the present study, we investigated exogenous spatial cuing following the presentation of auditory cues having different intensity profiles (looming or receding), waveforms (triangular structured waveform or white noise), and durations (250 ms or 500 ms). Auditory cues were presented from one of four locations (front-left, front-right, rear-left, or rear-right). The participants had to make speeded elevation discrimination responses to visual targets presented from the front (on the left or right). The magnitude of the cuing effect was larger following the presentation of a structured looming auditory cue than a structured receding cue. On the other hand, there was no statistical difference between the magnitude of the cuing effect in the looming and in the receding intensity profiles when white noise cues were used. Such findings are consistent with previous reports. Furthermore, the magnitude of the cuing effect was larger when the cues were presented from the front than from the rear. On the contrary, other recent findings showed that the presentation of a 100 ms constant-intensity auditory cue exogenously oriented visual attention to the cued hemifield, regardless of whether the cues were presented from the front or rear. Therefore, the findings reported here demonstrated that sound parameters can modulate the exogenous orienting of crossmodal spatial attention.